2014
DOI: 10.2967/jnumed.114.143297
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of 18F-FDG PET/CT for Staging Asymptomatic Breast Cancer Patients Younger Than 40 Years

Abstract: National Comprehensive Cancer Network guidelines consider 18F-FDG PET/CT for only clinical stage III breast cancer patients. However, there is debate whether TNM staging should be the only factor in considering if PET/CT is warranted. Patient age may be an additional consideration, because young breast cancer patients often have more aggressive tumors with potential for earlier metastases. This study assessed PET/CT for staging of asymptomatic breast cancer patients younger than 40 y. Methods In this Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
69
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 25 publications
7
69
1
2
Order By: Relevance
“…(18). Two other studies (1 including only breast cancer patients younger than 40 y) also showed that the yield from 18 F-FDG PET/CT was high starting in patients with clinical stage IIB disease (16,20). The results of these studies provide supportive evidence for a role of 18 F-FDG PET/CT in determining the stage of disease for high-and intermediate-risk patients (clinical stage IIB or higher).…”
Section: At Which Clinical Stage Should 18 F-fdg Pet/ct Be Initiated?supporting
confidence: 70%
“…(18). Two other studies (1 including only breast cancer patients younger than 40 y) also showed that the yield from 18 F-FDG PET/CT was high starting in patients with clinical stage IIB disease (16,20). The results of these studies provide supportive evidence for a role of 18 F-FDG PET/CT in determining the stage of disease for high-and intermediate-risk patients (clinical stage IIB or higher).…”
Section: At Which Clinical Stage Should 18 F-fdg Pet/ct Be Initiated?supporting
confidence: 70%
“…18 F-fluorodeoxyglucose positron emission tomographycomputed tomography (FDG PET/CT) has been important in the management of breast cancer patients [6]. It is used for screening for the extra-axillary lymph node metastasis [7] and distant metastasis [8,9], assessing for the treatment responses [10,11], and predicting prognosis [12], but the benefit of FDG PET/CT scanning for staging remains a matter of debate [13]. Several studies have suggested that the characteristics of FDG uptake in breast cancer are relevant to biological or histological attributes of primary tumor, including its biomarker status [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…For the initial staging work-up, many conventional imaging modalities, such as X-ray mammography, MR mammography, chest plain radiography, bone scintigraphy, and breast, axillary and liver ultrasonography, have been widely utilized. In recent years, several groups have evaluated the clinical role of FDG-PET/CT for pretreatment evaluation of breast cancer in comparison with conventional imaging tools [18,39,[43][44][45][46][47][48][49][50][51][52][53][54] (Table 2). These studies revealed that FDG-PET/CT is generally helpful, but particularly valuable for detection of extra-axillary (infraclavicular, supraclavicular and internal mammary) nodal metastasis and occult distant metastasis relative to conventional modalities, especially in patients with inflammatory breast cancer [43,46,47] and stage II-III disease [18, Fig.…”
Section: Initial Stagingmentioning
confidence: 99%